2020
DOI: 10.1186/s43141-019-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of Securidaca longipedunculata (Fresen) from shoot tip: an endangered medicinal plant

Abstract: Background Securidaca longipedunculata Fresen is an indigenous medicinal plant in Africa that has an important place in both traditional and modern medicine. This plant is endangered because of high seed dormancy, low germination rate, and over exploitation. Therefore, micropropagation method is important to address these problems. The objective of this study is to develop a micropropagation protocol for S. longipedunculata from shoot tip explants. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
5
11
0
Order By: Relevance
“…Half strength MS along with IAA 2.0 mg l À1 exhibited highest mean number of roots per shoot (11.40) and increased root length to the maximum (4.03 cm) (Figure 1d), while other concentrations of IAA caused antagonist effect on rhizogenesis in vitro in D. unguis-cati. Our results are in accordance with the studies carried out on Cichorium intybus [35], Digitalis lanata [36], Prosopis laevigata [37] and Securidaca longipedunculata [38]. The superiority of IAA over other auxins for induction of rhizogenesis has also been reported in Vanda pumila [39], Dendrobium chryseum [40], Phyllanthus tenellus [34].…”
Section: In Vitro Rhizogenesissupporting
confidence: 92%
“…Half strength MS along with IAA 2.0 mg l À1 exhibited highest mean number of roots per shoot (11.40) and increased root length to the maximum (4.03 cm) (Figure 1d), while other concentrations of IAA caused antagonist effect on rhizogenesis in vitro in D. unguis-cati. Our results are in accordance with the studies carried out on Cichorium intybus [35], Digitalis lanata [36], Prosopis laevigata [37] and Securidaca longipedunculata [38]. The superiority of IAA over other auxins for induction of rhizogenesis has also been reported in Vanda pumila [39], Dendrobium chryseum [40], Phyllanthus tenellus [34].…”
Section: In Vitro Rhizogenesissupporting
confidence: 92%
“…The effective superiority of one auxin over another within the nutrient media was attributed to the effective absorption and mobilization of the growth regulator or the rapid mobilization at the targeted sites [36]. The results of this study agree with those of Lijalem and Feyissa [37], which showed that different groups of growth regulators showed different responses in the formation of somatic embryos in Securidaca longipedunculota. They are also in agreement with the results of Gural et al [29] on Digitalis davisiana Heywood, showing that the presence of significant differences in the renewal of shoots depending on the explant type, plant type, hormonal combination and components of the basal medium, and the timing and requirements of growth regulators for the growth of somatic embryos differs according to the studied species [38].…”
Section: Selection Of the Best Hormonal Combinations For The Proporti...supporting
confidence: 83%
“…Interestingly, we noticed maximum shoot proliferation (72.2%) from node explant cultured onto MS forti ed with BAP @ 1 mg L -1 . Similar trends of ndings were also observed in Securidaca longipedunculata (Lijalem et al, 2020) and Trichosanthes dioica (Tiwari et al 2010). The nodal segment is considered to be the best explant type when compared to other types for initiation of direct shoot regeneration and proliferation and also requires only a lesser concentration of cytokinin, according to the Algabri et al survey (2019).…”
Section: Hardening Of In Vitro Raised Plantletssupporting
confidence: 80%